Soliton spin manipulation using an optical add_drop filter - S. Mitatha; S. Glomglome; C. Teeka; P. P. Yupapin (My University, 2012)
Abstract By using the optical add‐drop filter which is formed by a microring resonator.After a dark soliton pulse is fed into an input port of the add‐drop filter, the orthogonal soliton pair (dark and bright solitons) can be formed within the system and detected simultaneously at the output ports. Under the resonant condition, the conversion of dark and bright solitons corresponding to the left‐hand and right hand soliton orientations can be generated and seen. Whenever a soliton(photon) is absorbed by an object, an angular momentum of either +h or −h is imparted to the object, in which two possible soliton states known as soliton spins are exhibited and confirmed by the helical phase presentation. In application, the train of orthogonal solitons, that is, many solitons (photons) with slightly different wavelengths can be generated by using the modified add‐drop filter, which is available for many soliton spin investigations. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:1100–1103, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.26671
Keywords: Dissipative soliton; Advanced Fiber Laser Technologies